Radiotherapy plus immune checkpoint inhibitor in prostate cancer - Li, Tianjie; Qian, Xinye; Liu, Jinyang; Xue, Feng; Luo, Jing; Yao, Guanqun; Yan, Jun; Liu, Xiaodong; Xiao, Bo; Li, Jianxing (Frontiers in Oncology, 2023)
Immune checkpoint inhibitor (ICI) is a promising strategy for treating cancer. However, the efficiency of ICI mono-therapy is limited, which could be mainly attributed to the tumor microenvironment of the "cold" tumor. Prostate cancer, a type of "cold" cancer, is the most common cancer affecting men's health. Radiotherapy is regarded as one of the most effective prostate cancer treatments. In the era of immune therapy, the enhanced antigen presentation and immune cell infiltration caused by radiotherapy might boost the therapeutic efficacy of ICI. Here, the rationale of radiotherapy combined with ICI was reviewed. Also, the scheme of radiotherapy combined with immune checkpoint blockades was suggested as a potential option to improve the outcome of patients with prostate cancer.